PENGARUH WAKTU PROTEKSI INFUSA BIJI Persea americana Mill. TERHADAP HEPAR DAN GINJAL TIKUS TERINDUKSI KARBONTETRAKLORIDA - Lydia Setiawan; Inneke Devi Permatasari; Phebe Hendra (Sanata Dharma University, 2014)
Abstract: The aim of this research is to investigate the protective activity of the infusion of seed ofPersea americana Mill. (IBPA) against carbon tetrachloride-induced hepatotoxicity andnephrotoxicity in rats. Healthy rats were weighed and randomly divided into 6 groups of 5animals in each. Group 1 were treated with olive oil (2ml/kg, i.p) as negative control. Group 2received carbon tetrachloride (2 ml/kg, i.p.). Group 3 received IBPA 360.7 mg/kg once daily for 6hours (control of dose IBPA). Group 4-6 received IBPA at doses 360.7 mg/kg orally once for 1, 4and 6 hours respectively received treated carbon tetrachloride. Blood sample from all groupswas obtained by sinus orbitalis for the estimation serum transaminase and creatinine. Thepretreatment 1,4 and 6 hours of infusion of seed of Persea americana Mill. has a potent protectiveactivity upon carbon tetrachloride-induced hepatic and nephron damage in rats.Keywords: Persea americana Mill., infusion, protective, carbon tetrachloride